The influence of age and anthropometric variables on winning and losing in professional mixed martial arts - Kirk, Christopher (PeerJ Preprints, 2016)
Anthropometry and chronological age has been demonstrated to have an effect on individual performance in competitive sport, with the relationship between stature and wingspan being found to be selective criteria in many sports, although evidence for this in MMA is negligible. In this study, n = 278 professional MMA bouts were analysed with the winners and losers being compared in terms of chronological age, stature, wingspan, stature-to-wingspan ratio (S:W) and method of win/loss using paired samples t tests, Wilcoxon signed-rank tests, one way ANOVAs, Kruskal-Wallis tests (all ≤ .05) and Bayes Factor (BF 10). The results showed that for the most part anthropometric differences have no effect on who wins the bout, but taller bout losers are most likely to lose via strikes. The exception to this is at welterweight where taller participants were most likely to win, but with an anecdotal BF 10. Also at welterweight, participants with greater wingspans were most likely to lose via submission. Across the full cohort and several competitive divisions, it was found that older participants are significantly more likely to lose, and are also significantly more likely to lose via strikes. Participants who won via decision were found to be significantly older than those who won via strikes or submission.
Keywords: MMA; combat sports; aging; stature; ape ratio; wingspan